La mosquée de Paris. Construire l’islam français et l’islam en France, 1926-1947 - Naomi Davidson (Revue des Mondes Musulmans et de la Méditerranée)
The Paris Mosque and the Islamic Institute projects were initially conceived to honor the sacrifices of North African soldiers and intended for construction in the shadow of the Invalides. A few years later however, the mosque – rather a temple to ‘French Islam” than a memorial – was erected at the heart of the Latin Quarter. Indeed, the Mosque was thought to be the embodiment of a vision of Islam which would combine French and Muslim civilizations. "French Islam" based on a secular and republican model, was used as a means to manage and monitor the North African population in Paris in the 1920s and 1930s. The fact that French Islam was used as an intermediary made it obvious that French authorities could not envisage the possibility of Muslim secularity.In examining the construction of the Paris Mosque as well as mosques and other provincial Muslim religious sites in the 1940s, we see that the buildings themselves as well as their architectural and decorative styles helped to define the contours of French Islam and of Islam in France. During this period, the Paris Mosque as well as the provincial sites became the ground on which French administrations on both sides of the Mediterranean tried to construct rather different visions of metropolitan Muslim religion and practices while organizing a bureaucratic mechanism for the expression of Islam in France. The tension between the “French Islam” of the Parisian site and the “Islam in France” of certain provincial sites was evident not only in the speeches and debates that surrounded their creation, but also in the sites themselves. In metropolitan France, as I demonstrate, the mosque has been the symbol par excellence for defining the many different visions of Islam.